Studies of Antibacterials effect of Fresh Soft Coral (Geodia sp.) Extract Against Escherichia coli and Vibrio parahaemolyticus and The Content of Active Compounds - Faikoh, Elok Ning; Yuliana, Denok Eka; Suhendriani, Sari; Aini, Herlin Qurotul (Fakultas Teknologi Pertanian Universitas Brawijaya, 2013)
Soft corals (sponge) is a species of marine animals that live in the coral reef environment. There are more than five thousand species found in nature. The generally aims of this study are to diversify the utilization of diverse species of marine life in Indonesia through out knowledge about the chemical content and its bioactive characteristic especially sponge Geodia sp. The results showed that the crude extract of fresh soft corals Geodia sp. has antibacterial activity against E. coli and Vibrio parahaemolyticus. The most effective solvent to extract secondary metabolites in a fresh Geodia sp. is chloroform. The results of GC-MS analysis was found 16 secondary metabolites in soft corals Geodia sp,. Two of the most dominant are Androst-4-en-3-one at 34.06% and 1,5-di-tert-butyl-1 ,3-cyclohexadine at 17.96% and both of them are derivative of terpenoid.Keywords: soft corals, antibacterial, secondary metabolites